Association of IMPDH1 and IMPDH2 gene polymorphisms with efficacy and toxicity of mycophenolic acid treatment in renal transplant patients: a narrative review - Pratama, Dimo; Ikawati, Zullies; Hermawan, Adam (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2025)
Immunosuppressive regimen treatment in renal transplant recipients is necessary to prevent acute rejection from the body’s immune system. Mycophenolic acid (MPA), commonly prescribed for renal transplant recipients, exists in two formulations: mycophenolate mofetil (MMF) and enteric-coated mycophenolate sodium (EC-MPS). Both drugs act by inhibiting inosine-5’-monophosphate dehydrogenase (IMPDH), an enzyme that is responsible for the guanosine nucleotide synthesis pathway of T and B lymphocytes. IMPDH exists in two isoforms, IMPDH1 and IMPDH2, encoded by IMPDH1 and IMPDH2 gene, respectively. Polymorphisms in these genes may alter the enzyme activity, potentially influencing MPA pharmacodynamics and leading to variations in therapeutic responses among renal transplant patients taking MPA. A systematic literature search was performed using Scopus, PubMed, and Web of Science with the Boolean search strategy: “IMPDH AND Polymorphism* AND Mycophenol* AND ((Renal OR Kidney) Transplant* OR Graft*)”. The articles yielded from this literature search were screened, resulting in 15 articles that were included in this review. Some studies reported the association between the IMPDH1 or IMPDH2 polymorphism and acute rejection, while others found no significant correlation. Regarding toxicity, leukopenia was linked to IMPDH1 SNPs (rs2278293, rs2278294), although the results were inconsistent. Most of the studies found no significant association between IMPDH2 SNPs and leukopenia incidence.